Pendampingan Pelatihan Kelompok Budidaya Ikan Lele Barokah Di Desa Kesongo Kecamatan Tuntang Kabupaten Semarang - Ngatmin, Ngatmin (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This community service activity is an assistance that is packaged in the form of counselling. The activity focused on sharing experiences with residents of Kesongo Village, Tuntang District, Semarang Regency. The activity was held at the Kesongo Village Hall with the object of the community who are members of the catfish farming group. Participants who participated in this programme were initially targeted at 50 people from residents who have been involved in or have not been in the catfish farming business. There were about 35 participants or about 70% of the planned participants. The socialisation of this catfish farming mentoring training needs to be conveyed to the community at large. The more people who are involved in catfish cultivation, the more they will understand the importance of having a side business. In addition to the technical material presented related to catfish cultivation, business governance in the form of community-based groups and cooperatives was also delivered. Suggestions that can be given for this activity include that Kesongo Village residents continue to maintain a positive business climate in the catfish farming group. The abundant freshwater around Rawa Pening should be further enhanced. The more successful small home-based businesses will further improve the welfare of the community.